Efficacy of Dexamethasone as an Adjuvant for Scalp Nerve Blocks to Prolong Analgesia: A Prospective, Double-Blind, Randomized Controlled Study - Jia Z; Shrestha N; Wang S; Zhao C; Wang T; Luo F (Journal of Pain Research)
Zipu Jia,1 Niti Shrestha,2 Shuo Wang,3 Chunmei Zhao,2 Tao Wang,4 Fang Luo2 1Department of Day Surgery Center, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Pain Management, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Department of Anesthesiology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 4Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Fang Luo, Department of Pain Management, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China, Email 13611326978@163.comBackground: Scalp nerve blocks (SNB) may significantly reduce post-craniotomy pain (PCP) but only for a short period of time. Dexamethasone, as an adjuvant to local anesthetics, was reported to prolong the analgesia duration of never block; however, the addition of dexamethasone to SNB is rare. We therefore tested the hypothesis that dexamethasone as an adjuvant to bupivacaine in SNB is positive after craniotomy.Methods: Patients elective for craniotomy were randomly assigned to receive SNB with bupivacaine alone compared with dexamethasone and bupivacaine. The primary outcome was the duration of analgesia. The secondary outcomes include the cumulative amount of sufentanil consumption, the numeric rating scale (NRS), patient satisfaction score (PSS), the complications during the postoperative period, and SNB’s relevant adverse events.Results: There were 156 subjects included and 78 patients in each group (control and DEX group). The analgesia duration was significantly prolonged in the DEX group compared with the control group (660min (390,1005) vs 420min (314,504)) (p< 0.001). The postoperative sufentanil consumption was lower in the DEX group compared with the control group at 12h (P< 0.001), 24h (P=0.014), and 48h (P=0.049). The NRS scores were significantly lower in the DEX group compared with the control group at 8h (P< 0.001) and 12h (P=0.007) after craniotomy. From 4h to 16h postoperative, the PSS in the control group was lower than the DEX group (P < 0.05).Conclusion: Perineural dexamethasone as an adjuvant to bupivacaine without background glucocorticoid has the potential to improve the postoperative analgesic effect and patients’ satisfaction without serious complications after craniotomy.Keywords: post-craniotomy pain, scalp nerve block, peripheral dexamethasone, analgesia, postoperative